Design, Synthesis, Spectroscopic Characterization, HPLC Quantification, and In-Vivo Evaluation of Novel Thiazolidinedione Derivatives for Metabolic Syndrome - Sekar, Alexandar; Gade, Sandya Rani; Shah, Chanakya; Niroshini, C.; Sharma, Mrinal; Negi, Vipul; Sharma, Deepanshu; Yadav, Indraj Kumar; Vaishnav, Sushama (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Metabolic syndrome is a multifactorial metabolic disorder characterized by insulin resistance, obesity, dyslipidemia, hypertension, and chronic low-grade inflammation, substantially increasing the risk of type 2 diabetes mellitus and cardiovascular diseases. Although currently available thiazolidinediones (TZDs) improve insulin sensitivity through activation of peroxisome proliferator-activated receptor gamma (PPAR-γ), their clinical use is limited by adverse effects including weight gain, edema, and cardiovascular complications. Therefore, the development of safer and more potent TZD derivatives remains an important area of pharmaceutical research. Objective; The present study aimed to design, synthesize, spectroscopically characterize, quantitatively analyze, and evaluate the in vivo antimetabolic syndrome activity of novel thiazolidinedione derivatives. Materials and Methods: Novel thiazolidinedione derivatives were designed using molecular docking against the PPAR-γ receptor, followed by ADMET prediction and drug-likeness assessment. The target compounds were synthesized via Knoevenagel condensation and characterized using FT-IR, UV–Visible spectroscopy, ^1H NMR, ^13C NMR, LC-MS/MS, CHN elemental analysis, melting point determination, and thin-layer chromatography. A reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated according to ICH guidelines for quantitative estimation of the synthesized compounds. Antimetabolic syndrome activity was evaluated in a high-fat diet/streptozotocin-induced Wistar rat model by assessing biochemical, oxidative stress, inflammatory, and histopathological parameters. Results: Molecular docking demonstrated favorable binding affinities of all synthesized compounds toward the PPAR-γ receptor, with TDZ-3 exhibiting the highest docking score (−10.3 kcal/mol). The synthesized derivatives were obtained in satisfactory yields (72.4–91.8%) with high purity, and spectroscopic analyses confirmed their proposed molecular structures. The validated RP-HPLC method showed excellent specificity, linearity (R² = 0.9996), precision, accuracy, and robustness. In vivo studies demonstrated significant reductions in fasting blood glucose, HbA1c, HOMA-IR, total cholesterol, triglycerides, LDL, inflammatory biomarkers (TNF-α, IL-6, and CRP), and oxidative stress markers, while HDL levels and endogenous antioxidant enzymes (SOD, catalase, and GSH) were significantly increased. Histopathological examination further confirmed substantial restoration of normal liver, pancreas, adipose tissue, and kidney architecture, particularly in animals treated with TDZ-3. Conclusion: The present investigation demonstrated that the synthesized thiazolidinedione derivatives possess promising antihyperglycemic, antihyperlipidemic, antioxidant, and anti-inflammatory activities. Among the evaluated compounds, TDZ-3 emerged as the most promising lead candidate due to its superior molecular docking profile, favorable analytical characteristics, and significant pharmacological efficacy. These findings support the further pharmacokinetic, toxicological, and preclinical development of novel thiazolidinedione derivatives as potential therapeutic agents for the management of metabolic syndrome.
Keywords: Metabolic syndrome; Thiazolidinedione derivatives; PPAR-γ agonists; Molecular docking; RP HPLC; FT-IR; ^1H NMR; Spectroscopic characterization; Antidiabetic activity; Oxidative stress; Histopathology; Medicinal chemistry